Effects of a Multimedia-Enhanced GE Course on Undergraduate Computer Engineering Students' Development of Reading Skills and Growth Mindset - Shirazi, Niloufar; Rahimi, Mehrak (IEEE transactions on education, 2023)
Contribution: Research shows that nontechnical subjects like the English language have been neglected in computer science/engineering (CS/CE) education research. This study evaluates the effectiveness of a technology-enhanced general English (GE) course that exposed CE students to multimodal input during the prereading phase to develop their reading skills and growth mindset. Background: A wide range of technological affordances have been utilized and researched in teaching CE technical courses, however, English as an invaluable asset in CE students' academic and professional success is given lower priority. Research Questions: Do multimedia-enhanced prereading activities have a significant impact on CE students' development of reading skills and growth mindset? What are CE students' perceptions of multimedia-enhanced reading instruction? Methodology: The study compares the effects of incorporating multimedia in the prereading phase of a GE course with a conventional methodology. 137 undergraduate CE students participated in the study. Reading skills and growth mindset were assessed before and after the intervention. Qualitative data were obtained through structured interviews with 18 students of the experimental groups. Findings: Significant improvements in two reading skills, i.e., skimming and scanning were observed after the experiment. The effect size of the intervention was large for skimming, indicating that multimedia videos made understanding the gist of meaning easier for CE students. This finding was verified by the qualitative data as well. Also, the experiment had a significant impact on developing CE students' growth mindset, letting them vision their intelligence and talent as being fluid and malleable and, thus, changeable by effort and hard work.